2016
DOI: 10.1164/rccm.201510-2032pp
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Periostin in Respiratory Disorders

Abstract: Periostin is a matricellular protein that has been implicated in many disease states. It interacts with multiple signaling cascades to modulate the expression of downstream genes that regulate cellular interactions within the extracellular matrix. This review focuses on the role of periostin in respiratory diseases, including asthma and idiopathic pulmonary fibrosis, and its potential to help guide treatment or assess prognosis. Epithelial injury is a common feature of many respiratory diseases, resulting in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
129
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 69 publications
(94 reference statements)
3
129
1
6
Order By: Relevance
“…С учетом убедительных данных последних лет, показав-ших, что уровень сывороточного периостина может слу-жить в качестве системного биомаркера эозинофильного воспаления дыхательных путей, Th2-ассоциированного воспаления в респираторном тракте [61,62], а также что его уровень значительно повышен у детей с БА [63], следует продолжить исследование этого индикатора у детей с различными фенотипами свистящего дыхания. Возможно, оценка уровня сывороточного периостина позволит прогнозировать развитие БА при различных фенотипах свистящего дыхания или же с большей вероят-ностью диагностировать БА в раннем возрасте, посколь-ку есть данные, что у детей с БА экспрессия периостина эпителиальными клетками в 3,7 раза выше, чем у здоро-вых детей и детей с атопией, но без астмы [64].…”
Section: периостин как потенциальный маркер эозинофильного воспаленияunclassified
“…С учетом убедительных данных последних лет, показав-ших, что уровень сывороточного периостина может слу-жить в качестве системного биомаркера эозинофильного воспаления дыхательных путей, Th2-ассоциированного воспаления в респираторном тракте [61,62], а также что его уровень значительно повышен у детей с БА [63], следует продолжить исследование этого индикатора у детей с различными фенотипами свистящего дыхания. Возможно, оценка уровня сывороточного периостина позволит прогнозировать развитие БА при различных фенотипах свистящего дыхания или же с большей вероят-ностью диагностировать БА в раннем возрасте, посколь-ку есть данные, что у детей с БА экспрессия периостина эпителиальными клетками в 3,7 раза выше, чем у здоро-вых детей и детей с атопией, но без астмы [64].…”
Section: периостин как потенциальный маркер эозинофильного воспаленияunclassified
“…4 Periostin gene expression and protein synthesis is dynamic and rapidly turned over. It is induced by IL-4, IL-13, tumor growth factor (TGF)-β1,…”
mentioning
confidence: 99%
“…Periostin is a recognized biomarker in asthma, 3 and is useful for identification of patients with increased clinical benefit from treatment with anti-interleukin (IL)-13 and anti-immunoglobulin-E (IgE) therapy, 3 and may be prognostic for increased risk of asthma exacerbations and progressive lung function decline. 4 It is also a nascent biomarker in chronic obstructive pulmonary disease (COPD). 5 There is a need for further studies in asthma phenotypes and COPD, and in this issue of Polish Archives of Internal Medicine (Pol Arch Med Wewn), Katarzyna Górska et al 6 have extended the evaluation of periostin to include steroid-naive, mild-to-moderate asthma as well as COPD.…”
mentioning
confidence: 99%
“…1 Eosinophilic inflammation within the airways is usually considered as a hallmark of patients with asthma and it was found that the exacerbation rate was significantly reduced in patients with high levels of periostin. 2 While, to date, most studies have focused on periostin in asthma, its role in COPD is less clear and no information has been reported on blood levels of periostin in COPD patients in the context of exacerbation rates.…”
mentioning
confidence: 99%
“…Matching criteria included age, body mass index (BMI) and disease severity according to FEV 1 . Smoking was considered as additional confounder in the analysis because it has been reported recently that periostin may be repressed by smoking.…”
mentioning
confidence: 99%